Functional connectivity of hypothalamus in chronic migraine with medication overuse. (June 2019) - Lerebours, Fleur; Boulanouar, Kader; Barège, Michèle; Denuelle, Marie; Bonneville, Fabrice; Payoux, Pierre; Larrue, Vincent; Fabre, Nelly
Objective: To investigate the functional connectivity of the hypothalamus in chronic migraine compared to interictal episodic migraine in order to improve our understanding of migraine chronification. Methods: Using task-free fMRI and ROI-to-ROI analysis, we compared anterior hypothalamus intrinsic connectivity with the spinal trigeminal nucleus in patients with chronic migraine (n = 25) to age- and sex-matched patients with episodic migraine in the interictal phase (n = 22). We also conducted a seed-to-voxel analysis with anterior hypothalamus as a seed. Results: All patients with chronic migraine had medication overuse. We found a significant connectivity (T = 2.08, p = 0.024) between anterior hypothalamus and spinal trigeminal nucleus in the chronic group, whereas these two regions were not connected in the episodic group. The strength of connectivity was not correlated with pain intensity (rho: 0.09, p = 0.655). In the seed-to-voxel analysis, three regions were more connected with the anterior hypothalamus in the chronic group: The spinal trigeminal nuclei (MNI coordinate x = 2, y = −44, z = −62), the right dorsal anterior insula (MNI coordinate x = 10, y = 10, z = 18), and the right caudate (MNI coordinate x = 12, y = 28, z = 6). However, these correlations were no longer significant after whole brain FWE correction. Conclusion: An increased functional connectivity between the anterior hypothalamus and the spinal trigeminal nucleus, as previously reported in preictal episodic migraine, was demonstrated in chronic migraine with medication overuse. This finding confirms a major role of the anterior hypothalamus in migraine and suggests that chronic migraineurs are locked in the preictal phase.